Breaking down silos: On post-harvest loss interventions in Tanzania - Vandercasteelen, Joachim; Christiaensen, Luc (International Food Policy Research Institute, 2020)
This research examines the effects of an intervention aimed at reducing Post-Harvest Losses (PHL) of maize growing farmers during their maize storage in Tanzania. Farmers were invited to attend a training on best practices in post-harvest maize management, and a randomized subset of trainees received the opportunity to buy an improved storage facility (silos) at a substantially discounted price. Data collected at 30 days and 90 days after harvest, however, do not point to significant impacts of the treatments offered to the farmers. Receiving training on best practices improved stated knowledge but training nor the opportunity to purchase an improved storage had a significant effect on maize storage and sales behavior, physical PHL during storage, or the quality of the stored maize. The research explores potential explanations and provides some policy recommendations for future learning and decision-making on how to address PHL issues in developing countries.